Handbook of thermal analysis and calorimetry. Volume 5, - Brown, Michael E., 1938-; Gallagher, Patrick K. 1931- (Elsevier Science, 2008)
This is Volume 5 of an established handbook that covers the broad field of thermal analysis and calorimetry. Both these areas deal with the effect of heat on materials of all kinds, including biological materials, and are of interests to scientists and engineers across wide interdisciplinary boundaries. All chapters in all five volumes are written by international experts in the subject. The fifth volume covers recent advances in techniques and applications that complement the earlier volumes. The chapters refer wherever possible to earlier volumes, but each is complete in itself. Amongst the important new techniques that are covered are micro-thermal analysis, pulsed thermal analysis, fast-scanning calorimetery and the use of quartz-crystal microbalances.